APPRAISING THE INSTITUTIONAL FRAMEWORK FOR ENVIRONMENTAL MANAGEMENT IN NIGERIA - ONWUEMELE, Andrew (Journal of Environmental Management and Tourism; Vol 2 No 2 (2011): JEMT Volume II Issue 2(4) Winter 2011, 2011)
Environmental problems constitute one of the key development challenges in the African continent.The socioeconomic impact of environmental deterioration in Africa poses a major problem to development, stability, and daily lifestyles. Nigeria has a total land area of 983,213 square Kilometres with over 140 million people. The interaction of these millions of Nigerians with their respective environment has left indelible mark on the landscape. The manifestation of these impacts includes; urbanization, deforestation, desertification, overpopulation and all kinds of pollution. In response to this, successive governments in Nigeria have developed various institutional frameworks for environmental management. However, the impact of these institutions on environmental quality is yet to be felt as the level of environmental degradation continues to rise in different parts of the country. This paper appraises the institutional frameworks for environmental management in Nigeria with a view to improving its effectiveness in environmental management in Nigeria. The paper utilized both primary and secondary data sources. The primary data were obtained through indebt interview of key officials of environment ministry at the federal level while environmental documents and regulations of government were content analysed. The analysis of data shows weak institutional frameworks for environmental management arising from lack of coordination of environmental policies and responsibilities among various government ministries, weak capacity among staff of the various ministries, ineffectiveness of existing environmental policies, regulations and enforcement, political instability and lack of political will, frequent changes in policy and programmes, among other problems. The paper among others things calls for the establishment of an effective enforcement programme , development of clear mandate for enforcement among various ministries to avoid inter-ministry conflicts and capacity building of key staff in the environment ministries.